Analysis of the Influence of Work Stressors on Fatigue of Nurses in Inpatient Rooms, General Hospital of Haji Medan - Chairil Syadudin; Asyiah Simanjorang; Jamaludin Jamaludin; Lucia Lastiur (Journal La Medihealtico, 2021)
Work stress is caused by many factors from workplace, family, home, or environment. Excessive work stress will make someone anxious until developing excessive fatigue. Fatigue will decrease performance and increase work error rate that cause fatal workaccident.This study aimed to analyze influence of working stressors against nurses fatigue in patien room in haji hospital Medan. This study was quantitative method with a cross-sectional design, with a sample of 53 respondents. This study used questioners of the NIOSH Generic Job Stress Questionaire and Industrial Fatigue Research Committee which has been translated into Indonesian and has cheeked for validity and reliability. The results of the study regarding the influence work fatigue and work stress (P-value 0,000, r : 1,000), the influence workload and work fatigue (P-value 0,000, r : 1,000), the influence interpersonal conflict and work fatigue (P-value 0,000, r : 1,000), the influence job satisfaction and work fatigue (P-value 0,000, r : -0,588), the influence social support and work fatigue (P-value 0,000, r : -0,892), and based on the logistic regression test workload were variables the most influential, with an odds ratio of 94,5. The conclusion shows that workload is a variable that has strong influence on fatigue. Nurses with heavy workload are 94,5 times more likely to experience fatigue. So that the hospital needs to monitor and evaluate the performances of the nurses so the workload can be fixed and adjusted with the right capacity and ability of the nurses in providing services